Evaluation of Ophthalmoscopic Findings in Type 2 Diabetic Patients at a Tertiary Level Hospital (Bangladesh Medical Journal, 2023)
Diabetes mellitus (DM) is a global burden of disease. Long standing disease causes macrovascular and microvascular complications. Diabetic retinopathy (DR) is the most common microvascular complication of diabetes and it remains a leading cause of blindness and visual impairment in the working-age population in both developing and developed world. Patients with diabetes often developed other ophthalmic complications, such as corneal abnormalities, glaucoma, iris neovascularization, cataracts, and maculopathy. The study was carried out to evaluate the ophthalmoscopic changes in type-2 diabetes mellitus (T2DM) patients. This hospital based cross-sectional study was conducted in the department of Medicine, Shaheed Suhrawardy Medical College Hospital, Dhaka, from September 2018 to March 2019. Patients with T2DM attended at the department of medicine within the mentioned period were enrolled after fulfilling the selection criteria. Patients with dense, lentalopacities and other media opacities which prevented posterior segment examination were excluded from the study. Sample was selected by purposive sampling method. Detail demographic data were collected from the patients and recorded in structured case report form. Clinical examination and relevant investigations were done meticulously. Then pupil was dilated and ophthalmoscopic examination was done. Among the 50 diabetic patient’s male was 54%, middle aged (49-60 years) was 54% and sedentary workers was 84.0% with a positive family history of DM was 56.0%. Most of the patients were known hypertensive (64.0%) at the time of enrolment and almost all (94.0%) were taking antihypertensive drug. Retinal photography was performed in all patients and retinopathy was detected in 29 (58%) patients. Fundoscopic findings revealed that cotton-wool spots detected in 32.0% patients, Flame-shaped hemorrhages was 16.0% patients; Arteriovenous nipping was is 18.0% patients and opticdisc swelling (Papilloedema) in 26.0% patients. In this study 21 (42%) patients had normal fundoscopic findings. Retinopathy was more common in smoker (70.0%). Uncontrolled and long-standing diabetes and high HbA1c was major risk factors for the development of retinopathy (P < 0.001). In conclusion, diabetic retinopathy is more common in male smoker with uncontrolled and long-standing diabetic patients. T2DM is a major cause of blindness as it affects microvasculature of retina.Bangladesh Med J. 2021 Sept; 51(1): 33-40